1989
DOI: 10.1016/0014-5793(89)80743-4
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase gene expression in fibroblasts is regulated by a three‐dimensional contact with collagen

Abstract: Collagenase activity in fibroblasts is regulated by cytokines and the interaction with the extracellular matrix. In this study we demonstrate that fibroblasts cultured within a three-dimensional collagen gel show a strong induction of collagenase gene expression. In addition to increased de novo synthesis most of the secreted enzyme was found to be activated leading to a high collagenolytic activity and complete degradation of collagen matrices after removal of fetal calf serum. Collagen I gene expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(64 citation statements)
references
References 32 publications
4
60
0
Order By: Relevance
“…This was characterized by the presence of organized stress fibers within the cytoskeleton and an up-regulation of the anabolic gene (al(1) collagen). Loss of cytoskeletal organization through chemical disruption or a detachment of the gel resulted in an upregulation in the expression of the catabolic gene (interstitial collagenase) and an inhibition in the expression of the anabolic gene (al (1) [33,40,41,43,56].…”
Section: Discussionmentioning
confidence: 99%
“…This was characterized by the presence of organized stress fibers within the cytoskeleton and an up-regulation of the anabolic gene (al(1) collagen). Loss of cytoskeletal organization through chemical disruption or a detachment of the gel resulted in an upregulation in the expression of the catabolic gene (interstitial collagenase) and an inhibition in the expression of the anabolic gene (al (1) [33,40,41,43,56].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of studies showing that MMP-1 expression similarly depends on the mechanical signals by three-dimensional collagen lattices [22] and that integrin α # β " mediates both p38α activation [19] and MMP-1 expression induced by threedimensional collagen lattices [33], we hypothesized that p38α activation and MMP-1 expression might be related. To our surprise, the inhibition of p38α by SB203580 resulted in the bipolar pattern of MMP-1 expression induced by fl-coll (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also reported that the p38 MAPK is required for the induction of MMP-1 gene expression by ceramide and tumour-derived extracellular matrix metalloproteinase inducer (EMMPRIN) [20,21]. Interestingly, although contracting collagen lattices induce both activation of p38 MAPK [18] and expression of MMP-1 [3,22] in human fibroblasts, the complete inhibition of p38 MAPK by SB203580 at 10 µM does not result in appreciable suppression of MMP-1 expression [18].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the parameters that the two assays measure may be distinct. Cell invasion into collagen matrices is likely to be a more complex phenomenon than locomotion across a planar substrate, in terms of (i) cell-matrix interactions, (ii) actin cytoskeletal rearrangements in three-dimensions, (iii) modulation of intracellular signaling by a 3D collagen matrix (Roeckel and Krieg, 1994;Xu and Clark, 1997), and (iv) invasion and degradation of collagen (Mauch et al, 1989), and these dierences may explain the additional requirement for Cdc42 and Rho activity.…”
Section: Differential Signals In Motility and Invasionmentioning
confidence: 99%